Clinico-pathological study of cervical lymph nodes in children using ultrasound scan and FNAC: a hospital-based study - Ramana Reddy, G. V.; Mallikharjuna Reddy, M.; Reddy, Mittakanti Jawali; Prashanth, Dussa (International Surgery Journal, 2022)
Background: Cervical lymphadenopathy is one of the commonest clinical diagnostic dilemmas in children. The diagnosis plays key role in the management of cervical lymphadenopathy. Various methods of diagnosis include non-invasive and invasive procedures. Ultrasonography is a non-invasive readily available investigation for evaluation of cervical lymph nodes. One of the most reliable, less expensive diagnostic procedure is fine needle aspiration cytology (FNAC). Methods: A prospective study was conducted on 150 children in SVS Medical College Hospital, Mahabubnagar between January 2017 and January 2020. Ultrasonography followed by FNAC of lymph node was done in all children. Microsoft office excel software used for the data analysis. Sample size was calculated with 85% confidence level and 5% margin of error. Results: Out of 150 patients 79 were non-specific reactive lymphadenitis. 54 were granulomatous lymphadenitis.15 were lymphomas. 2 were malignant. Conclusions: Both ultrasonography and FNAC are very useful tools in the evaluation of cervical lymphadenopathy in children.